PEMBIAYAAN TALANGAN HAJI DALAM PERBANKAN SYARIAH DITINJAU DARI UNDANG-UNDANG PERBANKAN SYARIAH - FAISAL FANI NASUTION; MAHMUL SIREGAR; RAMLI SIREGAR (TRANSPARENCY, 2013)
Product of Fund of Roof-Gutter Haji represent the Product pertained a new innovation in Transaction some Moslem law Bank. This Product meant to close over the fund insuffiency which not yet answered the demand to candidate Haji by Loaning a number of money (Qardh) with the Guarantee of Deposit of Client of candidate Haji, last to the that loaning service Bank draw A number of Fee / ujrah (in this case Ijarah) as Religious advices DSN-MUI : Number 29/DSN-MUI/VI/2002, however in 2 (this two) akad happened the problems when application into Product of Fund of Roof-Gutter Haji to be explained after this, but before that it is better if evaluating one per one congeniality every akad that is Al-Qardh and Al-Ijarah. Problem of this research namely defrayal in Moslem law banking, hereinafter Defrayal of roof-gutter haji according to No. 21 year 2008 about Banking Moslem law and also protection punish to bank client in defrayal of roof-gutter haji evaluated from No. 21 Year 2008 About Moslem law Banking. This research use the approach of yuridis normative because this research use the data sekunder to analysis the contractual terms bank with  debitor and also its law protection aspect principally Moslem law. Bank Moslem law is the part of Banking Moslem law apart rom Business Unit Moslem law (UUS), while Bank Moslem law consisted of public Bank of Moslem law and Bank of Defrayal of Moslem Law People (BPRS). In of banking of Indonesia of Number 21 Year 2008 differentiating bank [of] pursuant to its business activity become two, that is bank executing business activity conventionally and bank executing business activity pursuant to Moslem law principle. No. 21 Year 2008 about Banking Moslem law not arrange peculiarly the defrayal of roof-gutter haji, at Section 21 only explaining business activity of Moslem law banking. this Roof-Gutter defrayal guaranteed by deposit had by client, client obliged to return a number of money loaned certain within. To the service of loaning of this roof-gutter haji fund, bank Moslem law get a run for the ( fee / ujrah) which is the level of not relied on  the amount of loaned fund. Protection of Client of fund of roof-gutter haji given early on namely with the existence of information of existence of bank Moslem law informatively, so that in have competition with the other bank will get the position which suitable and acceptable. Ambulatory protection early on better by giving information which its credibility accountable from all aspect.   Keyword : Pembiayaan Talangan Haji, Perbankan Syariah